Interiors: An Introduction - J. Nielson Karla (MC Graw Hill, 2007)
Interiors: An Introduction is the starting point for a lifetime of design education, appreciation, and enjoyment. Whether the goal is a career in interior design, or simply a better understanding of how to enhance one's own living space, the information and ideas in this text will help readers achieve it.